Antiproliferative and Proapoptotic Effects of Vitamin D3 in Human Neuroblastoma Cell Lines SH-SY5Y: An In-vitro Study - Kruti N Parikh; Kavitha Ramasamy; Kranthi Karunai Kadal; Punnagai Kumaravelu (Journal of Clinical and Diagnostic Research, 2023)
Introduction: Neuroblastoma is the most common and earliest childhood tumour with complicated biological and clinical characteristics. The treatment includes chemotherapy, radiation therapy, surgical resection, stem cell therapy and many other modes, making the management difficult to tolerate and unacceptable. Thereby increasing the need to develop novel therapies or repurpose already existing ones with anticancer potential. Many studies have shown that vitamin D3 has anticancer properties. Vitamin D3 receptors have been found in neuroblastoma cell lines, according to research. Anticancer property of vitamin D3 hasn’t been studied much in neuroblastoma cell lines. Aim: To evaluate the antiproliferative and proapoptotic effects of vitamin D3 on human neuroblastoma cell lines-SH-SY5Y. Materials and Methods: The present study was an in-vitro study in which human neuroblastoma cell lines SY5Y (a total of 2 cell lines) were obtained from National Centre for Cell Science (NCCS), Pune, Maharashtra, India, and control cells are cells from the cell lines that were left untreated. The antiproliferative effect of vitamin D3 in human neuroblastoma cell lines evaluated using the MTT (3-(4,5-dimethylthiazolyl-2)-2,5 diphenyltetrazolium bromide) assay. After 48 hours of incubation and treatment with six different (0.01, 0.1, 1, 10, 100, and 1000 ng/mL) concentrations of vitamin D3, the percentage of viable cells was determined using spectrophotometry and compared with control cells (untreated cells from cell lines). Different vitamin D3 (250 ng/mL, 500 ng/mL, 1000 ng/mL) doses were applied to cells and they were then incubated for 24 hours, Cell death and malformations were then observed using a phase contrast microscope, and Deoxyribonucleic Acid (DNA) fragmentation was investigated using gel chromatography. The obtained results were expressed as percentage of inhibition and tabulated in Microsoft Excel Sheet Version 16.16.27 and scatter plot graph was used to calculate IC50 (Half maximal inhibitory concentration). Results: The vitamin D3 showed antiproliferative property in SH-SY5Y cells at an IC50 of 164 ng/mL when tested against human neuroblastoma cells using the MTT assay. Phase contrast microscope demonstrated that vitamin D3 treated cells showed condensation of nuclei, shrinkage of the cytoplasm, convolution of outline and cell peeling demonstrating apoptosis. DNA fragmentation also showed typical DNA ladder formation confirming apoptosis in vitamin D3 treated cells, which showed that the treated cells’ DNA was more damaged than the control cells’ DNA. Conclusion: Vitamin D3 exhibited both proapoptotic and antiproliferative properties, as demonstrated by the MTT assay, Phase Contrast, and DNA fragmentation.